Insights into Nonalcoholic Fatty-Liver Disease Heterogeneity - Arrese, Marco; Arab, Juan P.; Barrera, Francisco; Kaufmann, Benedikt; Valenti, Luca; Feldstein, Ariel E. (Seminars in Liver Disease, 2021)
The acronym nonalcoholic fatty-liver disease (NAFLD) groups a heterogeneous patient population. Although in many patients the primary driver is metabolic dysfunction, a complex and dynamic interaction of different factors (i.e., sex, presence of one or more genetic variants, coexistence of different comorbidities, diverse microbiota composition, and various degrees of alcohol consumption among others) takes place to determine disease subphenotypes with distinct natural history and prognosis and, eventually, different response to therapy. This review aims to address this topic through the analysis of existing data on the differential contribution of known factors to the pathogenesis and clinical expression of NAFLD, thus determining the different clinical subphenotypes observed in practice. To improve our understanding of NAFLD heterogeneity and the dominant drivers of disease in patient subgroups would predictably impact on the development of more precision-targeted therapies for NAFLD.
Keywords: nonalcoholic fatty-liver disease; steatosis; cirrhosis; fibrosis; nonalcoholic; steatohepatitis; NAFLD; NASH; metabolic syndrome; heterogeneity